CRYO-RADIOTHERAPY FOR LOCAL LYADVANCED RECURRENT SKIN CANCER OF THE FACE - I. N. Pustynskiy; T. D. Tabolinovskaya; S. I. Tkachev; S. B. Alieva; R. I. Azizian; E. V. Kiva; A. V. Egorova; S. B. Peterson (Сибирский онкологический журнал, 2017)
The aim of the study was to improve the treatment outcomes for patients with locally advanced recurrent basal cell and squamous cell skin carcinomas of the face. Material and methods. A total of 26 patients with locally advanced recurrent basal cell (n=21) and squamous cell (n=5) skin carcinomas of the skin were treated with radiotherapy (2–2.5 Gy daily fractions to a total dose of 60–70 Gy, 5 days a week) in combination with local freezing of the tumor. Local cooling of the tumor to the temperature of tissue freezing was performed 10–15 minutes before each session of radiation therapy using liquid nitrogen cryo-preservation equipment. Patients with recurrent skin cancer who had received previously radiation therapy were not eligible for cryoradiotherapy. Results. Complete response was achieved in 23 (88.5 %) patients, residual tumors were removed by conventional surgery (n=2) and cryosurgery (n=1). At 2 to 14-year follow up, recurrences of skin cancer occurred in 3 (11.5 %) cases. Good aesthetic and functional results were observed. Conclusion. Cryo-radiotherapy was shown to be effective, providing long-term aesthetic and functional results.